Tratamiento clínico de un paciente con periodontitis crónica avanzada generalizada en la facultad de odontología de la Universidad de Antioquia, Medellín, Colombia: reporte de un caso (2012)
ABSTRACT: Periodontal disease affects the patient’s health altering the form, function, and esthetics of the stomatognathic system and producing huge deterioration in the person’s quality of life. This clinical case presents the comprehensive treatment of a 43-year-old male patient with generalized advanced chronic periodontitis including: non-surgical and surgical periodontal treatment and oral rehabilitation during a period of eighteen months by a senior undergraduate student and a group of professors specialized in periodontics and oral rehabilitation under the modality of teaching-social assistance at the School of Dentistry of Universidad de Antioquia (Medellín, Colombia).